Pengaruh Perubahan Massa Roller dan Konstanta Pegas Sistem Cvt Terhadap Daya dan Torsi Pada Sepeda Motor 109 Cc - Muhammad Fikri Alifudin; Purwoko Purwoko (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The development of the automotive industry is now experiencing a very rapid increase in the type of motorcycle. One of them is a motorcycle with automatic transmission or automatic motorcycle or CVT (Continously Variable Transmission). Matic motorcycle users often experience a lack of performance when used on daily trips. The mass of CVT rollers and springs is the main factor in the lack of performance of the matic motorcycle which is less efficient for its users. This research was conducted to determine the effect of increasing power and torque on motorcycles that are now declining in performance. The method used in this research is experimentation. Tests were carried out using a dynamometer tool to determine the comparison of the results of the variables carried out and compared to obtain maximum power and torque. The data obtained will be analyzed using statistical methods to evaluate the relationship between changes in roller mass and spring constant to power and torque. The results showed that the maximum power generated was at a roller variation of 11 grams and a spring constant of 33.78 N/cm of 7.19 HP at 6500 rpm engine speed. While the maximum torque is generated from the variation of roller 13 grams and spring 28.83 N / cm of 8.00 Nm at 6000 rpm engine speed.